Penentuan Kadar Kalsium (Ca) dalam Kulit dan Daging Buah Naga Merah (Hylocereus polyrhizus) yang Berasal dari Sidera - Miswan, Miswan; Said, Irwan; Ratman, Ratman (Jurnal Akademika Kimia, 2018)
This study aims to determine the calcium in peel and flesh of red dragon fruit (HylocereusPolyrhizus) Sample uses red dragon fruit aged 2 months, which is ripe on the tree. This research used the Spectrophotometric method, the analysis method based on the measurement of light absorption. Using spectro-direct as an instrument and tablet (Ca) as an indicator. From these studies, it was obtained in calcium levels: for peel was 9.21 mg/100 g and flesh red dragon fruit was 18.10 mg /100 g.